2010
DOI: 10.1159/000252779
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A: Clinical Manifestations and Management

Abstract: Due to improved living conditions and subsequent changes in hepatitis A epidemiology, the disease burden of hepatitis A is increasing in many regions. Recently, Korea has faced a large, community-wide outbreak of hepatitis A, which has prompted a vaccination program. The clinical spectrum of hepatitis A virus infection ranges from asymptomatic infection to fulminant hepatitis. Clinical manifestations depend on the age of the host: less than 30% of infected young children are symptomatic, while about 80% of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
172
0
14

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(188 citation statements)
references
References 49 publications
2
172
0
14
Order By: Relevance
“…38 There have been concerns about immune activation of different patient cohorts with immune-mediated disorders such as AA patients, patients with autoimmune hematological disorders and patients with rheumatic disorders. The support for these concerns is very limited and is only based on case reports, [39][40][41] while larger controlled studies in rheumatology patients have not shown an increased risk. 42,43 On the other hand, the response to vaccination in patients with very severe AA is likely to be poor.…”
Section: Vaccinationmentioning
confidence: 99%
“…38 There have been concerns about immune activation of different patient cohorts with immune-mediated disorders such as AA patients, patients with autoimmune hematological disorders and patients with rheumatic disorders. The support for these concerns is very limited and is only based on case reports, [39][40][41] while larger controlled studies in rheumatology patients have not shown an increased risk. 42,43 On the other hand, the response to vaccination in patients with very severe AA is likely to be poor.…”
Section: Vaccinationmentioning
confidence: 99%
“…The clinical course of acute hepatitis A is usually benign, and it is known that symptomatic treatment is sufficient for recovery 2. However, in rare cases, acute hepatitis A can be associated with serious complications which require prolonged hospitalization, and may result in death or liver transplantation 3. Cholestatic hepatitis is one of atypical clinical manifestations of acute viral hepatitis.…”
Section: Introductionmentioning
confidence: 99%
“…Cholestatic hepatitis is one of atypical clinical manifestations of acute viral hepatitis. Although it occurs only at a rate of 0.4~0.8%, protracted symptoms of anorexia, weight loss, pruritus, and jaundice are commonly associated 3. These clinical situations prolong the length of hospital stay, which causes increased medical expenses and social costs.…”
Section: Introductionmentioning
confidence: 99%
“…Both hepatitis A virus (HAV) and hepatitis E virus (HEV) are well known as enteric transmission hepatitis viruses [1][2][3][4][5][6]. Acute hepatitis due to HAV (AH-A) and HEV (AH-E) infections usually occurs in young people, both sporadically and epidemically, in developing countries.…”
Section: Introductionmentioning
confidence: 99%